2018
DOI: 10.1111/1440-1681.12939
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes on tissue healing in orthopaedic injuries

Abstract: Diabetes is a group of metabolic diseases characterized by hyperglycaemia resulting from the defective action or secretion of insulin. Chronic hyperglycaemia can lead to the damage, dysfunction and failure of various organs. In the context of complications of healing and orthopaedic rehabilitation, vascular (microangiopathy) and nerve (neuropathy) disorders deserve particular attention. About 12% of the patients admitted to orthopaedic departments have diabetes. Studies indicate that there is an indisputable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 86 publications
0
5
0
3
Order By: Relevance
“…These results verify the important role of tendon fibroblasts autophagy in tendon injury and might provide a new opportunity to As connective tissue, tendons connect muscles and bones, transfer loads between muscles and bones through complex compositions and a hierarchy composed mainly of collagen type I, and play an important role in the sports system (20). Emerging studies have shown that diabetes has complex effects on tendons and bones in a number of ways, including clinical manifestations (pain, stiffness, decreased range of motion), imaging abnormalities, and decreased biomechanical properties (structural and functional changes) (21). The process of diabetic tendon injury is complex and can involve abnormal immune response, angiogenesis, accumulation of advanced glycation end products (AGEs), and other extracellular matrix changes (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…These results verify the important role of tendon fibroblasts autophagy in tendon injury and might provide a new opportunity to As connective tissue, tendons connect muscles and bones, transfer loads between muscles and bones through complex compositions and a hierarchy composed mainly of collagen type I, and play an important role in the sports system (20). Emerging studies have shown that diabetes has complex effects on tendons and bones in a number of ways, including clinical manifestations (pain, stiffness, decreased range of motion), imaging abnormalities, and decreased biomechanical properties (structural and functional changes) (21). The process of diabetic tendon injury is complex and can involve abnormal immune response, angiogenesis, accumulation of advanced glycation end products (AGEs), and other extracellular matrix changes (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] These ovarian hormones alter collagen metabolism by generating enzymes that cleave and denature tropocollagen molecules. In addition, the effect of advanced glycation end products (AGEs), a phenomenon observed in the elderly and diabetic populations as responsible for the increased risk of ligament injuries, 69,70 could be a potential target using the proposed model. The viability of the model in detecting damage initiation may also help identify the differential and combined effects of the surgical and musculoskeletal factors that may contribute to the aberrant post-surgical ligament load.…”
Section: Discussionmentioning
confidence: 99%
“…Активация специфичного для остеобластов транскрипционного фактора RUNX2 (runt-related transcription factor 2) стимулирует дифференцировку остеобластов через регуляторный каскад AMPK/USF-1/SHP. Повышенная экспрессия RANKL (receptor activator for nuclear factor kappa-Β ligand) стимулирует остеокластогенез и подавляет остеобластогенез [16].…”
Section: механотрансдукция и механотерапия костной тканиunclassified
“…Существует бесспорная связь между диабетом и повышенным риском переломов, плохим заживлением повреждений костей, связок и мышечно-сухожильных пластин. Пови димому, одной из основных причин этого являет-ся неферментативное гликозилирование (гликирование) молекул коллагена, наблюдаемое в пожилых и диабетических популяциях, поскольку оно приводит к образованию конечных продуктов прогрессирующего гликирования [16].…”
Section: механотрансдукция и механотерапия костной тканиunclassified